CEMARAN Staphylococcus aureus PADA DAGING SAPI YANG DIPASARKAN DI PASAR TRADISIONAL KOTA BANDA ACEH (Staphylococcus aureus Contamination in Beef from Traditional Markets in Banda Aceh) - Jhon Leo Danubrata; Fakhrurrazi Fakhrurrazi; Maryulia Dewi; Sulasmi Sulasmi; Faisal Jamin; T. Armansyah TR; Nurliana Nurliana (Jurnal Medika Veterinaria, 2015)
This research aimed to determine the total amount of Staphylococcus aureus (S. aureus) contamination in beef sold in traditional market in Banda Aceh. Total of 16 beef samples were used in this research, 2 samples from Beurawe market, 10 samples from Peunayong market, and 4 samples from Seutui market. Samples were cultured on manitol salt agar. The number of S. aureus colonies was calculated using colony counter, and the result was compared to the limit of microbial contamination based on Indonesian National Standard (SNI). The result of this research showed that the highest level of S. aureus contamination was derived from Beurawe market. It is concluded that all beef sold by seller from traditional market in Banda Aceh were contaminated by S. aureus.Key words: Staphylococcus aureus, meat, traditional market, number of contamination